2021
DOI: 10.1093/g3journal/jkab115
|View full text |Cite
|
Sign up to set email alerts
|

The boom and bust of the aphid’s essential amino acid metabolism across nymphal development

Abstract: Within long term symbioses animals integrate their physiology and development with their symbiont. In a model nutritional mutualism, aphids harbor the endosymbiont, Buchnera, within specialized bacteriocyte cells. Buchnera synthesizes essential amino acids (EAA) and vitamins for their host, which are lacking from the aphid’s plant sap diet. It is unclear if the aphid host differentially expresses aphid EAA metabolism pathways and genes that collaborate with Buchnera for the production of EAA and vitamins throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Enterobacteriaceae is one of the important dominant taxa in the gut microbiota of many insects ( Wang et al, 2014 ; Yun et al, 2018 ; Raza et al, 2020 ). Enterobacteriaceae are involved in insect metabolism ( Pers and Hansen, 2021 ; Zhou et al, 2021 ), insect resistance or susceptibility to parasites, and pathogens and insecticides ( Oliver et al, 2003 ; Álvarez-Lagazzi et al, 2021 ; Polenogova et al, 2021 ) and play an important role in the host adaptability and reproduction of insects ( Shi et al, 2012 ; Wang et al, 2020b ). Pectobacterium , a clade of Enterobacteriaceae , is known as a function of nitrogen fixation ( Behar et al, 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae is one of the important dominant taxa in the gut microbiota of many insects ( Wang et al, 2014 ; Yun et al, 2018 ; Raza et al, 2020 ). Enterobacteriaceae are involved in insect metabolism ( Pers and Hansen, 2021 ; Zhou et al, 2021 ), insect resistance or susceptibility to parasites, and pathogens and insecticides ( Oliver et al, 2003 ; Álvarez-Lagazzi et al, 2021 ; Polenogova et al, 2021 ) and play an important role in the host adaptability and reproduction of insects ( Shi et al, 2012 ; Wang et al, 2020b ). Pectobacterium , a clade of Enterobacteriaceae , is known as a function of nitrogen fixation ( Behar et al, 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in Buchnera titer has previously been associated with different aphid clones 83 , plant diets 13 , increasing aphid nymphal age 82 , 84 , and heat shock 81 , 84 , 86 . Most obligate pathogens and symbionts, including Buchnera, overexpress the protein GroEL during non-heat shock conditions to rescue misfolded proteins 87 .…”
Section: Discussionmentioning
confidence: 96%
“…Our findings in this study raise the possibility that bacteriocyte polyploidy can enhance nutritional symbiosis between aphids and B. aphidicola , wherein both supply each other with nutrients that they cannot synthesize on their own [10, 19, 20] . Specifically, we predict that genes involved in amino acid metabolism, related to transport, and for symbiont regulation (e.g., lysozymes or cysteine-rich secreted proteins targeting bacteria), which have been reported to be highly expressed in the aphid bacteriomes [24, 25, 38, 40] , may be upregulated in a ploidy-dependent manner [6, 7, 47] . On the other hand, it is commonly known that cell volumes change depending on ploidy levels [6, 48] .…”
Section: Discussionmentioning
confidence: 99%
“…Pea-aphid, Acyrthosiphon pisum (Harris), is one of the best-studied aphid species in terms of life history (Figure 2, [29,30] ), polymorphism (Figure S1, [30][31][32] ), embryonic development [33][34][35] , nutritional symbiosis [23][24][25][36][37][38] , and genomics [39][40][41] . Detailed descriptions have focused on bacteriocyte development during aphid embryogenesis [21,22] , and it has been revealed that the number and volume of pea-aphid bacteriocytes increase during post-embryonic development ( [38,42] but see [43,44] ). These observations imply that aphid bacteriocytes are already polyploid at the end of embryogenesis and become hyper polyploid during post-embryonic development.…”
Section: Introductionmentioning
confidence: 99%